2018
DOI: 10.3390/cryst8020074
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Vibration of Layered GaTe Single Crystals

Abstract: Abstract:The effect of interlayer interaction on in-layer structure of laminar GaTe crystals was studied according to the lattice vibration using micro-Raman analysis. The results were also confirmed by the first principle calculations. Accordingly, the relationship between lattice vibration and crystal structure was established. Ten peaks were observed in the micro-Raman spectra from 100 cm −1 to 300 cm −1 . Eight of them fit Raman-active vibration modes and the corresponding displacement vectors were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The origin of these modes is still the subject of some controversy. Some previous first-principles calculations have suggested that these modes can be attributed to first 42 or second-order 15 Raman-active phonon modes, whereas other groups have claimed that they appear only as the products of the GaTe oxidation process. 19,25,26 In the latter case, the similarities to both TeO 2 and aged Raman spectra of other Te-containing compounds have been noted, 19 supporting the idea that the 129 and 144 cm –1 peaks result from the oxidation of Te atoms at the sample surface.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The origin of these modes is still the subject of some controversy. Some previous first-principles calculations have suggested that these modes can be attributed to first 42 or second-order 15 Raman-active phonon modes, whereas other groups have claimed that they appear only as the products of the GaTe oxidation process. 19,25,26 In the latter case, the similarities to both TeO 2 and aged Raman spectra of other Te-containing compounds have been noted, 19 supporting the idea that the 129 and 144 cm –1 peaks result from the oxidation of Te atoms at the sample surface.…”
Section: Resultsmentioning
confidence: 97%
“…The freshly cleaved sample shows prominent peaks at 109, 115, 162, 176, 210, 270, and 283 cm –1 in good agreement with previous reports. 25,26,42 Aged flakes exhibit only two peaks at 129 and 144 cm –1 . The origin of these modes is still the subject of some controversy.…”
Section: Resultsmentioning
confidence: 99%
“…Several experimental works have been devoted to the study of vibrational properties of stable gallium and indium tellurides. Most of them [33][34][35][36][37][38] consider the lattice vibrations of GaTe. Raman (R) active modes have been determined in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Raman (R) active modes have been determined in Refs. [33,37,38], infrared (IR) reflection spectrum has been measured in Refs. [35,36], and both R and IR frequencies of GaTe were obtained in Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation